UPAYA MENINGKATKAN HASIL BELAJAR OPERASI BILANGAN BULAT MELALUI MEDIA KONKRET DI SDN 4 MUARAKUANG - Sari, Erna (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
The problem in this study is whether the use and application of concrete media can iprove students' skills in integer operations in class V of Muarakuang 04 Elementary School? The purpose of this study was to determine the improvement of student learning outcomes about integer operations through concrete media. Of the 24 students, there were 17 students who successfully achieved the KKM score. In addition, there are 7 students who have not yet reached KKM. This means that the completeness achieved in Cycle I is 71%. In cycle II, the researcher made a decision to complete the research action and did not need to continue the research at the Cycle III stage due to the fulfillment of 86% KKM. The conclusion of the results of this study is that the application of concrete media can improve learning outcomes about integer operations in Class V students of SDN 4 Muara Kuang